Comparative Analysis of Five Moroccan Thyme Species: Insights into Chemical Composition, Antioxidant Potential, Anti-Enzymatic Properties, and Insecticidal Effects - Mohamed Ouknin; Hassan Alahyane; Naima Ait Aabd; Sara Elgadi; Youssef Lghazi; Lhou Majidi (Plants)
This study aimed to investigate the chemical composition and bioactivities of essential oils (EOs) from five Moroccan thyme species: Thymus broussonetii subsp. broussonetii, T. maroccanus, T. willdenowii, T. zygis subsp. gracilis, and T. satureioides, collected from various geographical regions. Gas chromatography–mass spectrometry (GC-MS) identified thymol, p-cymene, borneol, γ-terpinene, carvacrol, α-pinene, and camphene as major constituents, with variations across species. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) revealed important levels of calcium (450.6–712.2 mg/kg), potassium (255.4–420.7 mg/kg), magnesium (97.3–150.7 mg/kg), and iron (1.95–15.1 mg/kg). The EOs demonstrated strong antioxidant activity in DPPH, FRAP, and β-carotene bleaching assays. Insecticidal activity against Aphis gossypii revealed the highest efficacy with T. willdenowii EO (LC50 = 6.2 µL/mL), followed by T. maroccanus and T. zygis subsp. gracilis. Additionally, the EOs exhibited potent enzyme inhibitory effects at 1 mg/mL on acetylcholinesterase (83.1–96.4%), tyrosinase (77.5–89.6%), and α-glucosidase (79.4–89.5%). These findings suggest that thyme EOs, particularly from T. willdenowii, T. zygis, and T. maroccanus, are promising candidates for integrated pest management and natural enzyme inhibitors. Their potential applications in medicinal and pharmaceutical fields underscore the need for further research to optimize their use under specific conditions and dosages.